2019
DOI: 10.1108/heswbl-09-2018-0089
|View full text |Cite
|
Sign up to set email alerts
|

Graduate employability

Abstract: Purpose Following the outcry of several employers that many higher education (HE) graduates do not possess employability skills and therefore are not employable, the purpose of this paper, therefore, is to examine what the labour market (LM) actually demands from the higher education institutions (HEIs) and how the demands of the LM can be met by the HEIs in Nigeria. Design/methodology/approach The study is based on interviews and focus group with 28 university professors, executives of the students’ industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 38 publications
(48 reference statements)
0
22
0
Order By: Relevance
“…Drawing on these two key themes, it can be seen that participants placed a high value on establishing CAGC services centre in every TVET system, establishing effective linkages between the TVET system and industry, and promoting student-centred learning approaches that can encourage career learning and development. The participants suggested that the TVET curriculum should be revised to include up-to-date career development enhanced activities and programs to help students understand and pursue their career goals (in line with Okolie, Igwe, & Elom, 2019;Okolie, Nwosu, & Mlanga, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Drawing on these two key themes, it can be seen that participants placed a high value on establishing CAGC services centre in every TVET system, establishing effective linkages between the TVET system and industry, and promoting student-centred learning approaches that can encourage career learning and development. The participants suggested that the TVET curriculum should be revised to include up-to-date career development enhanced activities and programs to help students understand and pursue their career goals (in line with Okolie, Igwe, & Elom, 2019;Okolie, Nwosu, & Mlanga, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that Nigerian TVET graduates are not adequately equipped with the saleable skills required by employers (Mohammed & Ismail, 2015;Musa, 2010;Nwankwo, Obeta, & Nwaogbe, 2013). Studies have also linked Nigerian TVET graduate unemployment to poor career preparation of graduates (Okolie, Nwosu, & Mlanga, 2019;Okunuga & Ajeyalemi, 2018). This reflects poorly on the Nigerian HEIs' implementation of extracurricular activities and career development programs, such as work-placements, career fairs, CV preparation workshops, career networking, career mentoring, coaching on interview techniques, and support with job applications, which can foster students' career development, aspirations, and choices (Ojimba, 2012;Okolie, Nwosu & Mlanga, 2019;Oluwale, Jegede, & Olamade, 2013;Usman & Tyabo, 2013).…”
Section: Purpose Of Current Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These are important in that they aim to prepare students for their post-graduation lives (Graham, 2017;Holmes, 2013). The role of teaching staff is key for supporting or inhibiting students in the development of their employability (Knight & Yorke, 2003;Okolie, Nwosu, & Mlanga, 2019;Tsui et al, 1997).…”
Section: Teaching Staffmentioning
confidence: 99%
“…There is more and more concern that while graduates acquire significant subject knowledge when they leave universities and colleges, an important proportion of them may lack basic skills. Some of the areas considered to be areas in which graduates lack skills centre on planning, information technology (IT), literacy and communication (Okolie, Nwosu, and Mlanga, 2019;Shultz, 2008;Raybould & Sheedy, 2005). Numeracy is a critical skill required if graduates were to typify other employer requirements such as project management, planning and ability to work with uncertainty (Tymon, 2013;Black and Yasukawa, 2010;Raybould & Sheedy, 2005).…”
Section: Introductionmentioning
confidence: 99%